2022
DOI: 10.1007/s11914-022-00728-9
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Models of Osteocytes and Their Load-Induced Activation

Abstract: Purpose of Review Osteocytes are the conductors of bone adaptation and remodelling. Buried inside the calcified matrix, they sense mechanical cues and signal osteoclasts in case of low activity, and osteoblasts when stresses are high. How do osteocytes detect mechanical stress? What physical signal do they perceive? Finite element analysis is a useful tool to address these questions as it allows calculating stresses, strains and fluid flow where they cannot be measured. The purpose of this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 133 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Finite element fluid flow techniques and computational fluid flow dynamics (CFD) such as fluid-structure interaction (FSI) could offer promising approach for predicting the mechanical strain near implants [ 102 ]. By integrating the morphological architecture of the implant as well as that of the surrounding bone eg: ECM, LCN and vascular architectures in a FSI model, valuable insights on the impact of flow velocities and pressure regulation on the mechanical adaptation of the bone such as maximal principal strain, fluid shear stress and extent of osteocyte deformation upon perception of shear stress and the distribution of forces within the ECM can be obtained [ 103 , 104 ]. Alternatively, an approach would be to build a comprehensive multiscale model that incorporates the actual mechanical stress experienced by the bone during gait cycles [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finite element fluid flow techniques and computational fluid flow dynamics (CFD) such as fluid-structure interaction (FSI) could offer promising approach for predicting the mechanical strain near implants [ 102 ]. By integrating the morphological architecture of the implant as well as that of the surrounding bone eg: ECM, LCN and vascular architectures in a FSI model, valuable insights on the impact of flow velocities and pressure regulation on the mechanical adaptation of the bone such as maximal principal strain, fluid shear stress and extent of osteocyte deformation upon perception of shear stress and the distribution of forces within the ECM can be obtained [ 103 , 104 ]. Alternatively, an approach would be to build a comprehensive multiscale model that incorporates the actual mechanical stress experienced by the bone during gait cycles [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in-vivo studies have been unable to measure exact fluid velocity due to the inaccessibility of the LCN. Hence, the finite element method have been used to quantify the fluid velocity (Meslier and Shefelbine, 2023) (Steck et al, 2003) (Pereira et al, 2015)(Smit, 2022) (Kumar et al, 2011) (Van Tol et al, 2020) (Teresa et al, 2020). Recently, one study confirmed that Botox-induced muscle paralysis significantly affects the bone’s morphology (Gatti et al, 2019), leading to decreased fluid velocity around the osteocyte (Gatti et al, 2021), which motivates us to consider the loss of fluid flow for modelling bone loss.…”
Section: Introductionmentioning
confidence: 99%